SOME QUESTIONS OF COMPARATIVE STUDY OF SPEECH STAMPS OF UZBEK LANGUAGE - Mavlanova, Saida (Журнал иностранных языков и лингвистики, 2021)
This article discusses the importance of the role of the study of speech stamps, template sentence words and phraseological units in teaching the Uzbek language in schools and groups with the Russian language of instruction. In the textbooks, speech stamps are presented without translation into Russian, without explanation of in which speech situations it is necessary to use them, which was the basis for the conclusion that it is necessary to prepare a list of Uzbek speech stamps in the form of an Uzbek-Russian dictionary to provide students with this material.